A World of Nations: Notes on Internationalism, Ethnie Diversity and Folklore Scholarship in Four Countries - Klein, Barbro (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
Two particular problems are the focus of this article. One is that nations differ dramatically not only with regard to the ethnic diversity within their borders and the diversity politics pursued, but also with regard to the ways in which folklore scholars understand diversity, nationalism, and internationalism. The other concerns the differences between nations according to the premises for and the ideals of scholarship. These problems and issues are illustrated through sketches comparing history and folklore scholarship in four different countries: Estonia, Sweden, the United-States and Mali. We emphasize that folklorists in small or “peripheral” countries tend to acknowledge and analyze the role of folkloristics in shaping the symbols of their own nation, whereas contemporary folklorists in the “Occidental heartland”, i.e. the United States, seldom acknowledge the links between their own work and nation building. We argue that there is a hidden nation discourse in folklore study in the United States. But because this discourse is so inclusive of ethnic diversity, it seems far more international and open to the world beyond itself than it actually is. The article concludes with a plea for folklorists from all parts of the world to come together outside the anglophone institutions in the West, in order to examine critically their premises for scholarship and their notions of excellence and scholarly power.